ChemInform Abstract: Selective Oxidations of Activated Alcohols in Water at Room Temperature. Issue 8 (February 2015) - Lipshutz, B. H.; Hageman, M.; Fennewald, J. C.; Linstadt, R.; Slack, E.; Voigtritter, K.
Abstract Secondary allyl alcohols are unreactive under the investigated conditions allowing the selective oxidation of primary allylic alcohols in the presence of secondary allylic substrates.